Tanggung Jawab Pemerintah dalam Penyediaan Air Bersih bagi Masyarakat di Pulau Tanjung Melagan Kota Batam - Keyza Regita Fitani; Yudhanto Satyagraha Adiputra; Rizky Octa Putri Charin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The provision of clean water is a basic necessity and a fundamental responsibility of the government as a form of public accountability. Clean water not only plays a crucial role in supporting daily life but also directly affects public health, education, and economic productivity. However, the condition in Tanjung Melagan Island, located in the hinterland area of Batam City, still shows serious issues regarding access to clean water. Limited infrastructure, remote geographical location, and the lack of policy intervention are the main obstacles faced by the local community. This study aims to analyze the responsibility of the Batam City Government in providing clean water using J. Spiro’s accountability theory, which highlights three main indicators: accountability, obligation, and causality. This research employs a qualitative approach through in-depth interviews, field observations, and document studies. Informants in this study include officials from the Department of Human Settlements and Spatial Planning of Batam City, the Head of Galang Baru Subdistrict, and local residents of Tanjung Melagan Island. The results of the study indicate that the accountability of the Batam City Government in the provision of clean water has not been carried out substantively. Although formal forums such as Development Planning Meetings (Musrenbang) exist, their implementation remains procedural and does not fully absorb the aspirations and needs of the local population. The government's obligation to provide clean water is acknowledged normatively, but its realization often faces technical constraints, complex bureaucracy, and the delegation of responsibilities to non-governmental institutions. Furthermore, several underlying causes of this weak accountability were identified, including limited budgetary resources, poor inter-agency coordination, and low levels of community literacy and participation in planning and monitoring processes. Thus, this study emphasizes the importance of strengthening the role and capacity of local governments in providing essential services such as clean water, especially in underdeveloped and remote regions, to ensure that the principle of social justice is truly realized.